A nano-silicon dioxide microporous insulation board and preparation method thereof

By adding composite ceramic fibers and composite bonding agent to the nano-microporous insulation plate, the hollow whiskers and stable mesh structure are formed, which solves the problem of insufficient compressive and thermal insulation performance of the nano-microporous insulation plate, and realizes the high temperature conditions good mechanical properties are maintained.

CN118894710BActive Publication Date: 2024-12-20NANTONG ECOTHERM INSULATIONS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411390744.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-20
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The existing nano-microporous thermal insulation plates are insufficient in terms of compressive resistance and thermal insulation performance, and their mechanical properties are degraded under high temperature conditions.

Method used

Using the preparation method of nano-silica microporous insulating plate, the hollow whisker structure is formed by adding composite ceramic fibers and composite bonding agents, including the use of modified polysilazane fibers and silicon nitrogen ceramic fibers, and the formation of hollow whisker structures by ammonizing phenolic resins It forms a stable mesh structure with borosilicate sol to improve mechanical properties and thermal insulation properties.

Benefits of technology

The compressive resistance and thermal insulation performance of nano-microporous insulation plates are improved, and good mechanical properties are maintained under high temperature conditions, which reduces the influence of thermal insulation performance, and avoids shrinkage and mechanical properties under high temperature conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of building thermal insulation materials, and in particular to a nano-silica microporous thermal insulation board and a preparation method thereof. The nano-silica microporous thermal insulation board comprises the following raw materials in parts by weight: 22-25 parts of fumed silica, 4-5 parts of microporous calcium silicate, 4-5 parts of silicon carbide, 6-7 parts of composite ceramic fibers and 1-2 parts of composite binders. By adding the composite ceramic fibers and the composite binder, the mechanical properties of the microporous thermal insulation board can be improved due to the special fiber whisker structure of the composite ceramic fibers, while the hollow whisker structure ensures its thermal insulation performance under high temperature conditions, and the bonding ability of the composite binder under high temperature conditions avoids the problem of shrinkage and cracking of the microporous thermal insulation board caused by high temperature, solves the problem of insufficient compressive strength and thermal insulation performance of the existing nano-microporous thermal insulation board, and at the same time, the microporous thermal insulation board can still maintain good mechanical properties under high temperature conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building thermal insulation materials, and in particular to a nano-silicon dioxide microporous thermal insulation board and a preparation method thereof. Background Art

[0002] Nanoporous thermal insulation board is a kind of high-efficiency thermal insulation material developed in the past two years. It is developed based on the good thermal insulation performance of nanoporous materials. Its main components are raw materials such as fumed silica, silicon carbide, fiber and binder. Pure fumed silica has the defect of low strength, which leads to insufficient compressive capacity of the product and is prone to deformation and breakage during load-bearing applications. The compressive capacity of nanoporous thermal insulation board can be improved to a certain extent by increasing the amount of fiber. However, the fibers currently used in nanoporous thermal insulation boards are mostly glass fibers or alumina fibers. Due to the properties of the fibers themselves, excessive addition of the fibers will affect the thermal insulation performance of the nanoporous thermal insulation board. The common binder phenolic resin will shrink and fail under high temperature conditions, which will lead to cracking of the nanoporous thermal insulation board, thereby reducing the mechanical properties of the nanoporous thermal insulation board.

[0003] With the continuous improvement of product requirements, the performance of conventional nanoporous thermal insulation boards has gradually failed to meet market demand. Therefore, there is a need for a nanoporous thermal insulation board with good compressive resistance and thermal insulation performance, and which can maintain good mechanical properties under high temperature conditions. Summary of the invention

[0004] The purpose of the present invention is to provide a nano-silica microporous insulation board and a preparation method thereof, which solves the problem of insufficient compressive strength and thermal insulation performance of existing nano-microporous insulation boards, while still maintaining good mechanical properties under high temperature conditions.

[0005] The object of the present invention can be achieved by the following technical scheme: A method for preparing a nano-silica microporous insulation board, comprising the following steps: Step S1: weighing the following raw materials in parts by weight: 22-25 parts of fumed silica, 4-5 parts of microporous calcium silicate, 4-5 parts of silicon carbide, 6-7 parts of composite ceramic fibers and 1-2 parts of composite binder;

[0006] Step S2: mixing fumed silica, high specific surface area microporous calcium silicate, silicon carbide and composite ceramic fiber, stirring at a stirring rate of 800 rpm for 20-30 min, adding a composite binder and continuing to stir for 5-10 min, and then sending it into a hydraulic press, maintaining the pressure for 1 h at a pressure of 5 MPa, and then drying at a temperature of 130° C. for 4 h to obtain a nano-silica microporous insulation board;

[0007] The composite ceramic fiber is prepared by the following steps:

[0008] Step A1: Phenyl polysiloxane, octamethylcyclotetrasiloxane and tetramethylammonium hydroxide siliconate are mixed, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added under stirring at a rate of 300-400 rpm and a temperature of 120° C., and the mixture is reacted for 2 hours, and then the temperature is raised to 175° C. and the reaction is continued for 4-6 hours to obtain a siloxane chain extender, and the silazane oligomer and the siloxane chain extender are mixed, and the mixture is reacted for 4-5 hours under nitrogen protection at a stirring rate of 120-180 rpm and a temperature of 160° C. to obtain a modified polysiloxane;

[0009] The amount ratio of phenyl polysiloxane, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide silicon alkoxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1-1.2g:1.2-1.3mol:2-2.5g:1mol, and the amount ratio of silazane oligomer and siloxane chain extender is 25g:1-1.2g;

[0010] During the reaction, under the condition of tetramethylammonium hydroxide silicon alkoxide as a catalyst, octamethylcyclotetrasiloxane and phenyl polysiloxane undergo ring-opening polymerization, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added for end-capping to obtain a siloxane chain extender containing phenyl groups at the terminal amino group. Due to the presence of the terminal amino group in the siloxane chain extender, the siloxane chain extender participates in the copolymerization process of the silazane oligomer to obtain a modified polysilazane.

[0011] Step A2: The modified polysilazane is fed into a melt spinning machine and melt-spinned at a spinning temperature of 200°C, and then subjected to an infusible treatment by ultraviolet irradiation at a wavelength of 254 nm and an intensity of 110 μW / cm 2 Under the conditions, irradiate for 20 hours to obtain modified polysilazane fiber, then send the modified polysilazane fiber into a tubular furnace, and keep it warm for 2-2.5 hours at 1200°C under nitrogen protection to obtain silicon nitrogen ceramic fiber;

[0012] During the reaction, the modified polysilazane is spun by a melt spinning method, and then subjected to an infusible treatment by ultraviolet irradiation to obtain modified polysilazane fibers. Since there is a conjugated benzene ring in the modified polysilazane, the benzene ring is opened to generate a carbonyl group during the ultraviolet irradiation process, and the carbonyl group undergoes a nucleophilic addition reaction similar to aldol condensation with the silanol group in the modified polysilazane, thereby forming a cross-linked network structure, thereby achieving an infusible treatment, and then undergoing an inorganic treatment in a tubular furnace to obtain silicon nitrogen ceramic fibers;

[0013] Step A3: Mix vanadium pentoxide and anhydrous ethanol, ball-mill for 10-15 minutes, then add silicon nitrogen ceramic fiber, ammonium metatungstate and deionized water, ultrasonically disperse for 20 minutes, filter and freeze-dry to obtain a filter cake, immerse the filter cake in a mixed solution of silica sol and aluminum sol, vacuum impregnate and freeze-dry, and then send it into a sintering furnace for sintering, with a starting temperature of 50°C, heating to 1500°C at 5°C / min, and keeping the temperature at 1500°C for 2 hours to obtain a composite ceramic fiber;

[0014] The molar concentration of silicon in the mixed solution of silica sol and aluminum sol is 0.35 mol / L, the molar concentration of aluminum is 1.0 mol / L, and the dosage ratio of vanadium pentoxide, silicon nitrogen ceramic fiber and ammonium metatungstate is 0.8-1g: 20-22g: 0.4-0.5g:

[0015] During the sintering process, at 600-700℃, ammonium metatungstate is first decomposed into tungsten trioxide, while vanadium pentoxide melts to form a liquid phase and adheres to the silicon nitrogen ceramic fiber. At 900-1000℃, since the mixed liquid of silica sol and aluminum sol contains aluminum oxide, it reacts with tungsten trioxide to form tungsten aluminum oxide. Since the liquid phase formed by the melting of vanadium pentoxide can promote its growth, it grows preferentially on the surface of silicon nitrogen ceramic fiber. At the same time, it is continuously coated by aluminum-silicon-oxygen aggregates in the subsequent sintering process, thereby forming a whisker structure. At 1300-1500℃, the formed tungsten aluminum oxide decomposes to form a hollow whisker structure, and a composite ceramic fiber with hollow whiskers on the surface is obtained.

[0016] The composite binder is prepared by the following steps:

[0017] Step B1: Mix phenolic resin, 1,3-dibromopropane, potassium carbonate and acetonitrile, and react for 12 hours at a stirring rate of 300-400 rpm and a temperature of 82° C. to obtain a brominated phenolic resin; mix brominated phenolic resin, triethylenetetramine and ethanol, and react for 12 hours at a stirring rate of 300-400 rpm and a temperature of 80° C. to obtain an aminated phenolic resin;

[0018] The ratio of phenolic resin, 1,3-dibromopropane and potassium carbonate is 10-11 g: 0.1-0.11 mol: 13.5-14 g, and the ratio of brominated phenolic resin and triethylenetetramine is 3.4-3.5 g: 0.18-0.19 mol;

[0019] During the reaction, the phenolic hydroxyl group in the phenolic resin reacts with the bromine in 1,3-dibromopropane under the action of potassium carbonate to obtain a brominated phenolic resin, and the bromine in the brominated phenolic resin reacts with the amino group in triethylenetetramine to obtain an aminated phenolic resin.

[0020] Step B2: Boric acid, ethyl orthosilicate and anhydrous ethanol are mixed, and hydrochloric acid solution is added to adjust the pH value to 2.5, and the mixture is reacted for 3 hours at a stirring rate of 300-400 rpm and a temperature of 70°C, and then the temperature is raised to 80°C and the reaction is continued for 2 hours to obtain borosilicate sol, and the aminated phenolic resin and borosilicate sol are mixed, and the mixture is stirred at a stirring rate of 300-400 rpm and a temperature of 80°C, and boron powder is added, and the mixture is reacted for 3-4 hours to obtain a composite binder;

[0021] The mass fraction of the hydrochloric acid solution is 37%, the dosage ratio of boric acid, ethyl orthosilicate, anhydrous ethanol and deionized water is 0.25-0.3 mol: 1-1.1 mol: 80-85 mL: 24-28 mL, and the dosage ratio of aminated phenolic resin, borosilicate sol and boron powder is 4.2-4.5 g: 95-105 mL: 0.08-0.1 g;

[0022] During the reaction, under acidic conditions, a sol-gel method is used to form a silicon-oxygen-boron bond through hydrolysis condensation between boric acid and ethyl orthosilicate, thereby preparing a borosilicate sol, and then the aminated phenolic resin and the borosilicate sol are mixed and boron powder is added, the amine group in the aminated phenolic resin coordinates with the boron powder to form a coordination bond connection, and the silanol group in the borosilicate sol can also form a coordination bond connection with the boron powder, thereby preparing a composite binder;

[0023] Beneficial effects of the invention: The invention discloses a nano-silica microporous thermal insulation board and a preparation method thereof. By adding composite ceramic fibers and composite binders, the problems of insufficient compressive strength and thermal insulation performance of existing nano-microporous thermal insulation boards are solved, and at the same time, the board can still maintain good mechanical properties under high temperature conditions. The composite ceramic fibers are based on silicon nitrogen ceramic fibers, and hollow mullite whiskers grow on the surface of the composite ceramic fibers. Due to their special fiber whisker structure, when the microporous thermal insulation board is subjected to external stress, these whiskers can eliminate the internal stress at the fiber fixed joints to a certain extent by stretching, contracting, and bending, thereby improving the mechanical properties of the microporous thermal insulation board and making it have better compressive strength. Since the silicon nitrogen ceramic fibers are prepared by melt spinning, ultraviolet radiation infusibility treatment, and inorganic treatment of modified polysilazane, during the ultraviolet radiation infusibility treatment, a cross-linked network is formed between the modified polysilazane, so that the mechanical properties of the silicon nitrogen ceramic fibers after being ceramicized are greatly improved. At the same time, the presence of nitrogen in the silicon nitrogen ceramic fibers also improves the thermal insulation performance of the fibers themselves, and the hollow mullite whiskers grown on the surface of the composite ceramic fibers The stone whisker has good thermal insulation performance under high temperature conditions due to its hollow structure and its own properties, so that the composite ceramic fiber itself has good thermal insulation performance. From the multi-scale synergistic enhancement effect, while improving the mechanical properties of the microporous insulation board, it reduces the impact on the thermal insulation performance of the microporous insulation board. The composite binder is composed of ammoniated phenolic resin, borosilicate sol and boron powder. Since the composite binder contains borosilicate sol, it forms a silicon-oxygen tetrahedron with a stable mesh structure under high temperature conditions, thereby exerting a binding effect. It combines with the ammoniated phenolic resin to exert synergistic ability, so that the composite binder can maintain good bonding ability from low temperature to high temperature, thereby avoiding shrinkage and cracking of the microporous insulation board under high temperature conditions, resulting in a decrease in mechanical properties. Since the ammoniated phenolic resin and the borosilicate sol are connected by coordination bonds, the overall structure formed can better transmit mechanical properties and avoid the decrease in mechanical properties caused by dispersion problems. At the same time, the combination of organic and inorganic in the composite binder, after high-temperature curing, the boron-nitrogen-silicon-carbon structure formed can also play a certain insulation role. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1 A method for preparing a nano-silica microporous insulation board comprises the following steps: Step S1: weigh the following raw materials in parts by weight: 22 parts of TS610 fumed silica, 4 parts of commercially available 500-mesh microporous calcium silicate, 4 parts of commercially available 500-mesh silicon carbide, 6 parts of composite ceramic fibers and 1 part of a composite binder;

[0026] Step S2: mixing fumed silica, high specific surface area microporous calcium silicate, silicon carbide and composite ceramic fiber, stirring at a stirring rate of 800 rpm for 20 minutes, adding a composite binder and continuing to stir for 10 minutes, and then sending it into a hydraulic press, maintaining the pressure for 1 hour at a pressure of 5 MPa, and then drying at a temperature of 130° C. for 4 hours to obtain a nano-silica microporous insulation board;

[0027] The composite ceramic fiber is prepared by the following steps:

[0028] Step A1: commercially available IOTA-233 phenyl polysiloxane, octamethylcyclotetrasiloxane and tetramethylammonium hydroxide silicon alkoxide were mixed, stirred at a stirring rate of 300 rpm and a temperature of 120°C, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane was added, reacted for 2 hours, and then heated to 175°C and continued to react for 4 hours to obtain a siloxane chain extender. Commercially available Xinyuhong silazane oligomer and siloxane chain extender were mixed, and reacted for 4 hours under nitrogen protection at a stirring rate of 120-180 rpm and a temperature of 160°C to obtain a modified polysiloxane;

[0029] The amount ratio of phenyl polysiloxane, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide silicon alkoxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1g:1.2mol:2g:1mol, and the amount ratio of silazane oligomer and siloxane chain extender is 25g:1g;

[0030] Step A2: The modified polysilazane is fed into a melt spinning machine and melt-spinned at a spinning temperature of 200°C, and then subjected to an infusible treatment by ultraviolet irradiation at a wavelength of 254 nm and an intensity of 110 μW / cm 2 Under the conditions, the modified polysilazane fiber was irradiated for 20 hours to obtain the modified polysilazane fiber, and then the modified polysilazane fiber was sent into a tubular furnace, and kept warm for 2 hours at 1200°C under nitrogen protection to obtain silicon nitrogen ceramic fiber;

[0031] Step A3: Mix vanadium pentoxide and anhydrous ethanol, ball mill for 10 minutes, then add silicon nitrogen ceramic fiber, ammonium metatungstate and deionized water, ultrasonically disperse for 20 minutes, filter and freeze-dry to obtain a filter cake, immerse the filter cake in a mixed solution of commercially available KHZCM-30 silica sol and commercially available JWN-AS-2.5N01G aluminum sol, vacuum impregnate and freeze-dry, and then send it into a sintering furnace for sintering, with a starting temperature of 50°C, and heating to 1500°C at 5°C / min, and keeping it at 1500°C for 2 hours to obtain a composite ceramic fiber;

[0032] The molar concentration of silicon in the mixed solution of silica sol and aluminum sol is 0.35 mol / L, the molar concentration of aluminum is 1.0 mol / L, and the dosage ratio of vanadium pentoxide, silicon nitrogen ceramic fiber and ammonium metatungstate is 0.8 g: 20 g: 0.4 g:

[0033] The composite binder is prepared by the following steps:

[0034] Step B1: Mix commercially available Tengxuan Chemical 2123 phenolic resin, 1,3-dibromopropane, potassium carbonate and acetonitrile, and react for 12 hours at a stirring rate of 300 rpm and a temperature of 82° C. to obtain a brominated phenolic resin; mix the brominated phenolic resin, triethylenetetramine and ethanol, and react for 12 hours at a stirring rate of 300 rpm and a temperature of 80° C. to obtain an aminated phenolic resin;

[0035] The ratio of phenolic resin, 1,3-dibromopropane and potassium carbonate is 10g:0.1mol:13.5g, and the ratio of brominated phenolic resin and triethylenetetramine is 3.4g:0.18mol;

[0036] Step B2: Boric acid, ethyl orthosilicate and anhydrous ethanol are mixed, and hydrochloric acid solution is added to adjust the pH value to 2.5, and the mixture is reacted for 3 hours at a stirring rate of 300 rpm and a temperature of 70°C, and then the temperature is raised to 80°C and the reaction is continued for 2 hours to obtain borosilicate sol, and the aminated phenolic resin and the borosilicate sol are mixed, and the mixture is stirred at a stirring rate of 300 rpm and a temperature of 80°C, and boron powder is added and the mixture is reacted for 3 hours to obtain a composite binder;

[0037] The mass fraction of hydrochloric acid solution is 37%, the dosage ratio of boric acid, ethyl orthosilicate, anhydrous ethanol and deionized water is 0.25 mol: 1 mol: 80 mL: 24 mL, and the dosage ratio of aminated phenolic resin, borosilicate sol and boron powder is 4.2 g: 95 mL: 0.08 g.

[0038] Example 2 A method for preparing a nano-silica microporous insulation board comprises the following steps: Step S1: weigh the following raw materials in parts by weight: 25 parts of TS610 fumed silica, 5 parts of commercially available 500-mesh microporous calcium silicate, 5 parts of commercially available 500-mesh silicon carbide, 6 parts of composite ceramic fibers and 2 parts of composite binder;

[0039] Step S2: mixing fumed silica, high specific surface area microporous calcium silicate, silicon carbide and composite ceramic fiber, stirring at a stirring rate of 800 rpm for 30 minutes, adding a composite binder and continuing to stir for 5 minutes, and then sending it into a hydraulic press, maintaining the pressure for 1 hour at a pressure of 5 MPa, and then drying at a temperature of 130° C. for 4 hours to obtain a nano-silica microporous insulation board;

[0040] The composite ceramic fiber is prepared by the following steps:

[0041] Step A1: commercially available IOTA-233 phenyl polysiloxane, octamethylcyclotetrasiloxane and tetramethylammonium hydroxide silicon alkoxide were mixed, stirred at a stirring rate of 400 rpm and a temperature of 120°C, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane was added, reacted for 2 hours, and then heated to 175°C and continued to react for 4 hours to obtain a siloxane chain extender. Commercially available Xinyuhong silazane oligomer and siloxane chain extender were mixed, and reacted for 4 hours under nitrogen protection at a stirring rate of 180 rpm and a temperature of 160°C to obtain a modified polysiloxane;

[0042] The amount ratio of phenyl polysiloxane, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide silicon alkoxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.2g:1.2mol:2g:1mol, and the amount ratio of silazane oligomer and siloxane chain extender is 25g:1.2g;

[0043] Step A2: The modified polysilazane is fed into a melt spinning machine and melt-spinned at a spinning temperature of 200°C, and then subjected to an infusible treatment by ultraviolet irradiation at a wavelength of 254 nm and an intensity of 110 μW / cm 2 Under the conditions, the modified polysilazane fiber was irradiated for 20 hours to obtain the modified polysilazane fiber, and then the modified polysilazane fiber was sent into a tubular furnace, and kept warm for 2.5 hours at 1200°C under nitrogen protection to obtain silicon nitrogen ceramic fiber;

[0044] Step A3: Mix vanadium pentoxide and anhydrous ethanol, ball mill for 10 minutes, then add silicon nitrogen ceramic fiber, ammonium metatungstate and deionized water, ultrasonically disperse for 20 minutes, filter and freeze-dry to obtain a filter cake, immerse the filter cake in a mixed solution of commercially available KHZCM-30 silica sol and commercially available JWN-AS-2.5N01G aluminum sol, vacuum impregnate and freeze-dry, and then send it into a sintering furnace for sintering, with a starting temperature of 50°C, and heating to 1500°C at 5°C / min, and keeping it at 1500°C for 2 hours to obtain a composite ceramic fiber;

[0045] The molar concentration of silicon in the mixed solution of silica sol and aluminum sol is 0.35 mol / L, the molar concentration of aluminum is 1.0 mol / L, and the dosage ratio of vanadium pentoxide, silicon nitrogen ceramic fiber and ammonium metatungstate is 1g:22g:0.4g:

[0046] The composite binder is prepared by the following steps:

[0047] Step B1: Mix commercially available Tengxuan Chemical 2123 phenolic resin, 1,3-dibromopropane, potassium carbonate and acetonitrile, and react for 12 hours at a stirring rate of 300 rpm and a temperature of 82° C. to obtain a brominated phenolic resin; mix the brominated phenolic resin, triethylenetetramine and ethanol, and react for 12 hours at a stirring rate of 400 rpm and a temperature of 80° C. to obtain an aminated phenolic resin;

[0048] The ratio of phenolic resin, 1,3-dibromopropane and potassium carbonate is 11g:0.1mol:13.5g, and the ratio of brominated phenolic resin and triethylenetetramine is 3.5g:0.18mol;

[0049] Step B2: Boric acid, ethyl orthosilicate and anhydrous ethanol are mixed, and hydrochloric acid solution is added to adjust the pH value to 2.5, and the mixture is reacted for 3 hours at a stirring rate of 400 rpm and a temperature of 70°C, and then the temperature is raised to 80°C and the reaction is continued for 2 hours to obtain borosilicate sol, and the aminated phenolic resin and the borosilicate sol are mixed, and the mixture is stirred at a stirring rate of 300 rpm and a temperature of 80°C, and boron powder is added, and the mixture is reacted for 3 hours to obtain a composite binder;

[0050] The mass fraction of hydrochloric acid solution is 37%, the dosage ratio of boric acid, ethyl orthosilicate, anhydrous ethanol and deionized water is 0.25 mol: 1.1 mol: 85 mL: 24 mL, and the dosage ratio of aminated phenolic resin, borosilicate sol and boron powder is 4.5 g: 95 mL: 0.1 g.

[0051] Example 3 A method for preparing a nano-silica microporous insulation board comprises the following steps: Step S1: weigh the following raw materials in parts by weight: 25 parts of TS610 fumed silica, 5 parts of commercially available 500-mesh microporous calcium silicate, 5 parts of commercially available 500-mesh silicon carbide, 7 parts of composite ceramic fibers and 2 parts of composite binder;

[0052] Step S2: mixing fumed silica, high specific surface area microporous calcium silicate, silicon carbide and composite ceramic fiber, stirring at a stirring rate of 800 rpm for 30 minutes, adding a composite binder and continuing to stir for 10 minutes, and then sending it into a hydraulic press, maintaining the pressure for 1 hour at a pressure of 5 MPa, and then drying at a temperature of 130° C. for 4 hours to obtain a nano-silica microporous insulation board;

[0053] The composite ceramic fiber is prepared by the following steps:

[0054] Step A1: commercially available IOTA-233 phenyl polysiloxane, octamethylcyclotetrasiloxane and tetramethylammonium hydroxide silicon alkoxide were mixed, stirred at a stirring rate of 400 rpm and a temperature of 120°C, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane was added, reacted for 2 hours, and then heated to 175°C and continued to react for 6 hours to obtain a siloxane chain extender. Commercially available Xinyuhong silazane oligomer and siloxane chain extender were mixed, and reacted for 5 hours under nitrogen protection at a stirring rate of 180 rpm and a temperature of 160°C to obtain a modified polysiloxane;

[0055] The amount ratio of phenyl polysiloxane, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide silicon alkoxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.2g:1.3mol:2.5g:1mol, and the amount ratio of silazane oligomer and siloxane chain extender is 25g:1.2g;

[0056] Step A2: The modified polysilazane is fed into a melt spinning machine and melt-spinned at a spinning temperature of 200°C, and then subjected to an infusible treatment by ultraviolet irradiation at a wavelength of 254 nm and an intensity of 110 μW / cm 2 Under the conditions, the modified polysilazane fiber was irradiated for 20 hours to obtain the modified polysilazane fiber, and then the modified polysilazane fiber was sent into a tubular furnace, and kept warm for 2.5 hours at 1200°C under nitrogen protection to obtain silicon nitrogen ceramic fiber;

[0057] Step A3: Mix vanadium pentoxide and anhydrous ethanol, ball mill for 15 minutes, then add silicon nitrogen ceramic fiber, ammonium metatungstate and deionized water, ultrasonically disperse for 20 minutes, filter and freeze-dry to obtain a filter cake, immerse the filter cake in a mixed solution of commercially available KHZCM-30 silica sol and commercially available JWN-AS-2.5N01G aluminum sol, vacuum impregnate and freeze-dry, and then send it into a sintering furnace for sintering, with a starting temperature of 50°C, and heating to 1500°C at 5°C / min, and keeping the temperature at 1500°C for 2 hours to obtain a composite ceramic fiber;

[0058] The molar concentration of silicon in the mixed solution of silica sol and aluminum sol is 0.35 mol / L, the molar concentration of aluminum is 1.0 mol / L, and the dosage ratio of vanadium pentoxide, silicon nitrogen ceramic fiber and ammonium metatungstate is 1g:22g:0.5g:

[0059] The composite binder is prepared by the following steps:

[0060] Step B1: Mix commercially available Tengxuan Chemical 2123 phenolic resin, 1,3-dibromopropane, potassium carbonate and acetonitrile, and react for 12 hours at a stirring rate of 400 rpm and a temperature of 82° C. to obtain a brominated phenolic resin; mix the brominated phenolic resin, triethylenetetramine and ethanol, and react for 12 hours at a stirring rate of 400 rpm and a temperature of 80° C. to obtain an aminated phenolic resin;

[0061] The ratio of phenolic resin, 1,3-dibromopropane and potassium carbonate is 11g:0.11mol:14g, and the ratio of brominated phenolic resin and triethylenetetramine is 3.5g:0.19mol;

[0062] Step B2: Boric acid, ethyl orthosilicate and anhydrous ethanol are mixed, and hydrochloric acid solution is added to adjust the pH value to 2.5, and the mixture is reacted for 3 hours at a stirring rate of 400 rpm and a temperature of 70°C, and then the temperature is raised to 80°C and the reaction is continued for 2 hours to obtain borosilicate sol, and the aminated phenolic resin and the borosilicate sol are mixed, and the mixture is stirred at a stirring rate of 400 rpm and a temperature of 80°C, and boron powder is added and the mixture is reacted for 4 hours to obtain a composite binder;

[0063] The mass fraction of hydrochloric acid solution is 37%, the dosage ratio of boric acid, ethyl orthosilicate, anhydrous ethanol and deionized water is 0.3 mol: 1.1 mol: 85 mL: 28 mL, and the dosage ratio of aminated phenolic resin, borosilicate sol and boron powder is 4.5 g: 105 mL: 0.1 g.

[0064] Comparative Example 1 Compared with Example 3, this comparative example replaces the phenyl polysiloxane in the preparation process of the composite ceramic fiber in Example 3 with commercially available Xinyuhong S11210215 methyl polysiloxane, and the other steps are the same.

[0065] Comparative Example 2 Compared with Example 3, this comparative example is different in that the vanadium pentoxide in the preparation process of the composite ceramic fiber in Example 3 is replaced by aluminum fluoride, and the other steps are the same.

[0066] Comparative Example 3 Compared with Example 3, this comparative example is to remove the ammonium metatungstate in the preparation process of the composite ceramic fiber in Example 3, and the other steps are the same.

[0067] Comparative Example 4 Compared with Example 3, this comparative example replaces the ammoniated phenolic resin in the preparation process of the composite binder in Example 3 with commercially available Tengxuan Chemical 2123 phenolic resin, and the other steps are the same.

[0068] Take the nano-silica microporous insulation boards prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, and make them into 360mm×255mm×20mm samples. The thermal conductivity of the samples at 200°C and 1000°C is measured by a flat plate thermal conductivity tester. The samples are kept at 1000°C for 10 hours, and the linear shrinkage of the samples is calculated. The samples are then placed in a microcomputer-controlled test press, and pressure is applied to the samples at a constant pressure speed to compress them to 90% of their original size. The compressive strength is recorded and calculated. The test results are shown in Table 1. Test result table:

[0069] Table 1 Test results

[0070] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 <![CDATA[Thermal conductivity at 200 °C (W·m -1 ·K -1 ).]]> 0.035 0.033 0.032 0.037 0.053 0.038 0.35 <![CDATA[Thermal conductivity at 1000 °C (W·m -1 ·K -1 ).]]> 0.060 0.059 0.057 0.061 0.092 0.072 0.64 Linear shrinkage (%) 1.23 1.21 1.21 1.47 1.63 1.22 1.52 Compressive strength (MPa) 0.39 0.42 0.43 0.34 0.29 0.42 0.25

[0071] It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, Comparative Example 1 replaces the phenyl polysiloxane in the preparation process of the composite ceramic fiber of Example 3 with methyl polysiloxane. Due to the lack of phenyl, its crosslinking degree decreases during the infusible treatment process, which in turn causes the mechanical properties of the composite ceramic fiber to decrease, thereby affecting the mechanical properties of the microporous insulation board. Comparative Example 2 replaces vanadium pentoxide in the preparation process of the composite ceramic fiber of Example 3 with aluminum fluoride. Due to the lack of vanadium pentoxide, mullite whiskers do not preferentially grow on the fibers, which leads to a significant decrease in the thermal insulation performance and mechanical properties of the microporous insulation board. Comparative Example 3 removes ammonium metatungstate in the preparation process of the composite ceramic fiber of Example 3. Due to the lack of ammonium metatungstate, the mullite whiskers cannot form a hollow result, which leads to a decrease in the thermal insulation performance of the microporous insulation board under high temperature conditions. Comparative Example 4 When the ammoniated phenolic resin in the preparation process of the composite binder in Example 3 is replaced by phenolic resin, the mechanical properties of the microporous insulation board under high temperature conditions are significantly reduced due to the lack of coordination bond connection.

[0072] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0073] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a nano-silicon dioxide microporous insulation board, characterized in that: The method comprises the following steps: Step S1: weighing the following raw materials in parts by weight: 22-25 parts of fumed silica, 4-5 parts of microporous calcium silicate, 4-5 parts of silicon carbide, 6-7 parts of composite ceramic fibers and 1-2 parts of composite binder; Step S2: Mix fumed silica, microporous calcium silicate, silicon carbide and composite ceramic fiber, stir at a stirring rate of 800 rpm for 20-30 min, add a composite binder and continue stirring for 5-10 min, then put it into a hydraulic press, maintain the pressure for 1 h at a pressure of 5 MPa, and then dry it at a temperature of 130° C. for 4 h to obtain a nano-silica microporous insulation board; The composite ceramic fiber is prepared by the following steps: Step A1: Phenyl polysiloxane, octamethylcyclotetrasiloxane and tetramethylammonium hydroxide silicon alkoxide are mixed, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added under stirring at a rate of 300-400 rpm and a temperature of 120° C., and the mixture is reacted for 2 hours, and then the temperature is raised to 175° C. and the reaction is continued for 4-6 hours to obtain a siloxane chain extender, and a silazane oligomer and a siloxane chain extender are mixed, and the mixture is reacted for 4-5 hours under nitrogen protection at a stirring rate of 120-180 rpm and a temperature of 160° C. to obtain a modified polysilazane; Step A2: The modified polysilazane is fed into a melt spinning machine and melt-spinned at a spinning temperature of 200°C, and then subjected to an infusible treatment by ultraviolet irradiation at a wavelength of 254 nm and an intensity of 110 μW / cm 2 Under the conditions, irradiate for 20 hours to obtain modified polysilazane fiber, then send the modified polysilazane fiber into a tubular furnace, and keep it warm for 2-2.5 hours at 1200°C under nitrogen protection to obtain silicon nitrogen ceramic fiber; Step A3: Mix vanadium pentoxide and anhydrous ethanol, ball-mill for 10-15 minutes, then add silicon nitrogen ceramic fiber, ammonium metatungstate and deionized water, ultrasonically disperse for 20 minutes, filter and freeze-dry to obtain a filter cake, immerse the filter cake in a mixed solution of silica sol and aluminum sol, vacuum impregnate and freeze-dry, and then send it into a sintering furnace for sintering, with a starting temperature of 50°C, heating to 1500°C at 5°C / min, and keeping the temperature at 1500°C for 2 hours to obtain a composite ceramic fiber; In step A1: the amount ratio of phenyl polysiloxane, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide silicon alkoxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1-1.2 g: 1.2-1.3 mol: 2-2.5 g: 1 mol, and the amount ratio of silazane oligomer and siloxane chain extender is 25 g: 1-1.2 g; In step A3: the molar concentration of silicon in the mixed solution of silica sol and aluminum sol is 0.35 mol / L, the molar concentration of aluminum is 1.0 mol / L, and the amount ratio of vanadium pentoxide, silicon nitrogen ceramic fiber and ammonium metatungstate is 0.8-1g:20-22g:0.4-0.5g; The composite binder is prepared by the following steps: Step B1: Mix phenolic resin, 1,3-dibromopropane, potassium carbonate and acetonitrile, and react for 12 hours at a stirring rate of 300-400 rpm and a temperature of 82° C. to obtain a brominated phenolic resin; mix brominated phenolic resin, triethylenetetramine and ethanol, and react for 12 hours at a stirring rate of 300-400 rpm and a temperature of 80° C. to obtain an aminated phenolic resin; Step B2: Boric acid, ethyl orthosilicate and anhydrous ethanol are mixed, and hydrochloric acid solution is added to adjust the pH value to 2.5, and the mixture is reacted for 3 hours at a stirring rate of 300-400 rpm and a temperature of 70°C, and then the temperature is raised to 80°C and the reaction is continued for 2 hours to obtain borosilicate sol, and the aminated phenolic resin and borosilicate sol are mixed, and the mixture is stirred at a stirring rate of 300-400 rpm and a temperature of 80°C, and boron powder is added, and the mixture is reacted for 3-4 hours to obtain a composite binder; In step B1, the ratio of phenolic resin, 1,3-dibromopropane and potassium carbonate is 10-11 g: 0.1-0.11 mol: 13.5-14 g, and the ratio of brominated phenolic resin and triethylenetetramine is 3.4-3.5 g: 0.18-0.19 mol; In step B2: the mass fraction of the hydrochloric acid solution is 37%, the amount ratio of boric acid, ethyl orthosilicate, anhydrous ethanol and deionized water is 0.25-0.3 mol: 1-1.1 mol: 80-85 mL: 24-28 mL, and the amount ratio of aminated phenolic resin, borosilicate sol and boron powder is 4.2-4.5 g: 95-105 mL: 0.08-0.1 g.

2. A nano-silicon dioxide microporous insulation board, characterized in that: Prepared according to the preparation method of claim 1.

Citation Information

Cited By

  • Body-enhanced nano thermal insulation board and preparation method thereof

    CN121800467A